Ordinance No. 8, in Los Angeles Herald, April 12, 1889, at 7 - (:unkn) unknown (My University, 1889)
Ordinance No. 8-An Ordinance to Amend an Ordinance Entitled an "Ordinance Regulating the Carrying of Deadly or Dangerous Weapons," §§ 1-2. Approved April 10, 1889; In Force April 12, 1889. Volume 32, Number 10. (Los Angeles, CA): Prohibited concealed carry of any dirk, Bowie-knife, sword-cane, pistol, revolver, or any other dangerous or deadly weapon.
Keywords: CARRY - CONCEALED